2014
DOI: 10.1590/s0100-83582014000400015
|View full text |Cite
|
Sign up to set email alerts
|

Chemical control of Pileamicrophylla in cattleya seedlings (Cattleyatenebrosa x Cattleyaleopoldy)

Abstract: -Species of the orchidaceae family are grown for marketing flowers and among them the genus Cattleya stands out. However, due to its slow growth, the substrate is subjected to weed infestation. Therefore, this study aims to evaluate the selectivity and efficiency of herbicides in controlling Pilea microphylla in Cattleya orchid seedlings (Cattleya tenebrosa x Cattleya leopoldy). We used a completely randomized design with four replications. The evaluated herbicides were oxyfluorfen (0, 120, 240 and 480 g ha ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…and/or superior. Battistus et al (2014) also found the same result in Cattleya orchid's seedlings (Cattleyatenebrosa x Cattleya leopoldy), being selective to the seedlings of floriferous and performing control of P. microphylla (above 90%) in 14 DAA for doses equal and/or superior to 120 g ha -1 a.i. In another study, Freitas et al (2007b) …”
Section: Resultssupporting
confidence: 58%
“…and/or superior. Battistus et al (2014) also found the same result in Cattleya orchid's seedlings (Cattleyatenebrosa x Cattleya leopoldy), being selective to the seedlings of floriferous and performing control of P. microphylla (above 90%) in 14 DAA for doses equal and/or superior to 120 g ha -1 a.i. In another study, Freitas et al (2007b) …”
Section: Resultssupporting
confidence: 58%
“…They observed that no tested treatment provided any type of injury to both orchid species, and herbicide doses higher than 0.250 g ha -1 were efficient to control this weed. Battistus et al (2014) also studied the control of rockweed in orchids with the herbicide oxyfluorfen, but on cattleya (Cattleya tenebrosa x Cattleya leopady) seedlings with the herbicides nicosulfuron, mesotrione, clethodim, flumioxazin, and metsulfuron-methyl. The researchers reported that all herbicides were selective for this cattleya hybrid, but the herbicides flumioxazin, metsulfuron-methyl, and oxyfluorfen were also efficient for weed control, corroborating the results of oxyfluorfen obtained by Freitas et al (2007).…”
Section: Orchidsmentioning
confidence: 99%
“…(Romani et al 2013), and orchids (Cattleya species, Epidendrum ibaguense H.B.K., Dendrobium spp.) (Battistus et al 2014;Freitas et al 2007).…”
mentioning
confidence: 99%